2018
DOI: 10.1155/2018/8463569
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Safety and Functional Outcomes of Anterior versus Retropupillary Iris-Claw IOL Fixation

Abstract: Purpose To compare the functional and clinical outcomes of the iris-claw intraocular lens (IOL) placed on the anterior versus posterior surface of the iris. Patients and Methods A multicenter, retrospective study. Data on eyes that underwent anterior or retropupillary iris-claw IOL implantation because of inadequate capsular support secondary to complicated cataract surgery, trauma, and dislocated/opacified IOLs since January 2015 were analyzed. For study inclusion, evaluation results had to be available in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
2
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 17 publications
4
67
2
6
Order By: Relevance
“…Compared with AC IOL, retro-iris implantation is the main advantage of scleral-fixated PC IOL. Therefore, damage of the endothelial cells and the angle structures can be avoided [ 1 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with AC IOL, retro-iris implantation is the main advantage of scleral-fixated PC IOL. Therefore, damage of the endothelial cells and the angle structures can be avoided [ 1 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Mora et al compared the functional and clinical outcomes of the iris-claw IOL placed on the anterior and posterior surfaces of the iris. They showed that fixing the iris-claw IOL on the anterior or posterior chamber is equally effective and safe for aphakic eyes with inadequate capsular support [ 30 ]. Other reports showed no changes in cECC after iris-fixed lens implantation when compared with sulcus-fixated lens implantation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may result from large posterior capsular contact of IOL and constant tension of zonular fibers brought by haptics, which together lead to good IOL centering with less dislocation [28, 29]. Several special IOLs including iris-claw IOL, iris fixation posterior chamber-IOL (PC-IOL) and IOL with stabilizing haptics should be recommended to enhance the stability [30, 31]. Some surgical improvements like suspensory IOL implantation and IOL clamping at capsulorhexis are also helpful for visual rehabilitation [32].…”
Section: Discussionmentioning
confidence: 99%